Hannah Arendt : A crise na educação como crise da modernidade - Freitas, Mayara de (2019)
This thesis proposes as a problem of study the crisis in modern education addressed by Hannah Arendt. Its main objective is to study the judgment of the crisis in education as a crisis of the political world in modernity. Arendt's political thought sought some of his resonances in the context of contemporary education to reflect on political alienation as a founding element of the crisis. To this end, it was important to understand how the categories “authority” and “birth” are articulated in the construction of the Arendtian discourse on education. The study starts from the role of depoliticization and "not thinking" in education as representatives of the alienation of being in the public world, which also requires attention to the categories: "speech", "action", "thinking" and "responsibility". This is a pertinent discussion that refers to the meaning of educational activity and pedagogical activity as communication with the new generations. It is noteworthy that the space of action and discourse is political and has an important role for being to exist, demonstrating the singularity in the condition of plural in humanity. Thinking about it, the alienation is not thinking as a consequence of renouncing the ability to build spaces of politics. And the originality of the contributions inherent in Arendt's thought to the reflections on the crisis in education, allow an awakening of ethical-political responsibility inherent in the educational act before the public world.